The witchcraft trial in Moscow - Adler, Friedrich; Commission of Enquiry into the Conditions of Political Prisoners (London : Labour Publications Department, 1936)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: politieke gevangenen; justitie; Sovjet-Unie.